2016
DOI: 10.26582/k.48.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a physical education-based dynamic stretching program on hamstring extensibility in female high-school students

Abstract: The aim of the present study was to examine the effects of a dynamic stretching development program followed by a four-week detraining period and maintenance program on hamstring extensibility in a physical education setting. A sample of 108 female high-school students aged 16-17 years from four classes were clustered randomly and assigned to either an experimental or a control group. During physical education sessions, the experimental group students performed a dynamic stretching program twice a week for eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…We completely disagree with the opinion of these authors. A bouncing-type movement is simply one of the possibilities within a range of dynamic stretching techniques [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We completely disagree with the opinion of these authors. A bouncing-type movement is simply one of the possibilities within a range of dynamic stretching techniques [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among young people the practice of dynamic techniques has been rejected because of a greater potential risk of muscle injury [ 28 ]. Nevertheless, as several authors suggest [ 27 , 29 ], dynamic stretching exercises may not be harmful when practiced gently.…”
Section: Discussionmentioning
confidence: 99%
“…The sitting hip flexion and supine decubitus exercises with the knees extended were selected in some studies, due to the equilibrium conditions that guarantee during the execution and the stability of the knee in extension (Becerra-Fernández et al, 2016;Mayorga-Vega et al, 2015;Rodríguez et al 1999Rodríguez et al , 2008Sainz de Baranda, 2009;Useros & Campos, 2011). In addition to these postures some studies perform standing exercises (Mayorga-Vega et al, 2015;Nelson & Bandy, 2004;Reid & McNair, 2004;Useros & Campos, 2011).…”
Section: Stretching Exercises and Stretching Techniquementioning
confidence: 99%
“…Nevertheless, as several authors suggest (e.g., Behm et al, 2011;Turki-Belkhiria et al, 2014), dynamic stretching exercises may not be harmful when practiced in a soft and controlled way. In this line, three studies showed the effectiveness and safety of a dynamic stretching program (Becerra-Fernández et al, 2016;Van Rensburg & Coetzee, 2014;Vidal, 1995). Two studies were interested in determining whether there was a significant difference among the static and dynamic stretching techniques (Van Rensburg & Coetzee, 2014;Vidal, 1995).…”
Section: Stretching Exercises and Stretching Techniquementioning
confidence: 99%
See 1 more Smart Citation